(untitled) (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
A textbook is one of the essential learning sources for EFL/ESL learners, especially in vocabulary acquisition. It must be evaluated and selected when performing eight categories (aims and approaches, design and organization, language content, skill, topic, methodology, teacher’s book, and practical considerations). The language content category evaluates whether the EFL/ESL materials used in the learning process for vocabulary teaching are adequate in terms of vocabulary quality and range, the emphasis placed on vocabulary development, and strategies for individual learning. It is possible to say that learning a language is fundamental and so deeply dependent on vocabulary. This study is aimed to identify the number of lexical units found in the reading materials of an EFL textbook, Developing English Competencies 3, and to measure the sufficiency of lexical units found in the reading materials of the textbook in vocabulary quantity and range by comparing to the general frequency list, Michael West’s GSL (1953). The book became the object of this descriptive quantitative study with the specific linguistic field, corpus. A computational tool, RANGE, and FREQUENCY, designed by Nation (2001) and then developed by Heatley, Nation, and Coxhead (2002) was applied to count the lexical units easily. It was found that the book was clearly imbalanced concerning the amount of 5,064 tokens and 1,434 types with the distribution of 57.1% in range one, 14.9% in range two, and 5.2% in range three throughout three ranges described by Nation. In summary, the book didn’t propose the foreign learners’ expectations and necessary opportunities for automatizing vocabulary. Besides, it is also limited to offering all possible comprehensive situations, which the students may find in real life